The Influence Of Communication And Work Discipline On Job Satisfaction And Employee Performance (Study At PT.Omega Mas Pasrepan Pasuruan) - Muhammad Alfarizi (SEAN Institute, 2023)
Human resources are one of the assets that play an important role in achieving company goals. Human resources are company assets that must be maintained. PT. Omega Mas is a company engaged in wood production by producing handmade wooden furniture and accessories. This study aims to determine the influence between the variables studied. These variables include work discipline, job satisfaction, and employee performance. This type of research uses quantitative methods. The sample in this study is the entire population of operational sites in the company as many as 193 employees/respondents. The analysis technique used is the Path analysis technique using the SPSS 25 application. The results show that work discipline has a positive and significant effect on employee performance with a coefficient of 0.156 and a p value of 0.049. And job satisfaction has no significant positive effect on employee performance with a coefficient of 0.139 and a p value of 0.105.